Bile Acid Diarrhea and NAFLD: Shared Pathways for Distinct Phenotypes. Issue 4 (9th February 2020) - Weaver, Michael J.; McHenry, Scott A.; Sayuk, Gregory S.; Gyawali, C. Prakash; Davidson, Nicholas O.
Abstract : Irritable bowel syndrome with diarrhea (IBS‐D) and NAFLD are both common conditions that may be influenced by shared pathways of altered bile acid (BA) signaling and homeostatic regulation. Pathophysiological links between IBS‐D and altered BA metabolism include altered signaling through the ileal enterokine and fibroblast growth factor 19 (FGF19) as well as increased circulating levels of 7α‐hydroxy‐4‐cholesten‐3‐one, a metabolic intermediate that denotes increased hepatic BA production from cholesterol. Defective production or release of FGF19 is associated with increased BA production and BA diarrhea in some IBS‐D patients. FGF19 functions as a negative regulator of hepatic cholesterol 7α‐hydroxylase; therefore, reduced serum FGF19 effectively de‐represses hepatic BA production in a subset of IBS‐D patients, causing BA diarrhea. In addition, FGF19 modulates hepatic metabolic homeostatic response signaling by means of the fibroblast growth factor receptor 4/klotho beta receptor to activate cascades involved in hepatic lipogenesis, fatty acid oxidation, and insulin sensitivity. Emerging evidence of low circulating FGF19 levels in subsets of patients with pediatric and adult NAFLD demonstrates altered enterohepatic BA homeostasis in NAFLD. Conclusion: Here we outline how understanding of shared pathways of aberrant BA homeostatic signaling may guide targeted therapies in some patients with IBS‐D and subsets of patients with NAFLD. Abstract : Here, we review current knowledge on the intersections and shared signaling pathways associated with diarrhea‐predominant irritable bowel syndrome, bile acid diarrhea, and NAFLD. These signaling pathways are centered on disturbed enterohepatic bile acid homeostasis, and in particular, ileal enterokine signaling via FGF19.